Mathematical Model of Vertical Transmission of Hepatitis B with the Effect of Treatment and Vaccination - Latifah, Meilina Latifah; Helma (Department of Mathematics, Universitas Negeri Padang (UNP), 2023)
Hepatitis B is a type of liver inflammation caused by infection with the Hepatitis B virus (HBV). Vertical transmissions can transmit hepatitis B. The precautions that can be taken to avoid vertical transmission of Hepatitis B are curable with treatment and vaccination. The goal of this research is to learn the mathematical model of Hepatitis B vertical transmission by observing the effects of treatment and vaccination, stability analysis, and interpreting the analysis results from the model. This research is essential. Points of equilibrium were discovered based on the model analysis. Through treatment and vaccination, vertical transmission of Hepatitis B will not become epidemic, according to the conclusions of this mathematical model's investigations. Meanwhile, as more and more effective contacts between infected individuals and vulnerable individuals occur and the average number of sexual partners per infected adult female, the vertical transmissions of Hepatitis B will grow.